Human Chondrocyte Activation by Toxins From Premolis semirufa, an Amazon Rainforest Moth Caterpillar: Identifying an Osteoarthritis Signature - Villas-Boas, Isadora M.; Pidde, Giselle; Lichtenstein, Flavio; Ching, Ana Tung Ching; Junqueira-de-Azevedo, Inácio de Loiola Meirelles; DeOcesano-Pereira, Carlos; Madureira Trufen, Carlos Eduardo; Chudzinski-Tavassi, Ana Marisa; Morais, Kátia Luciano Pereira; Tambourgi, Denise V. (Frontiers in Immunology, 2020)
Pararamosis is a disease that occurs due to contact with the hairs of the larval stage of the Brazilian moth Premolis semirufa. Envenomation induces osteoarticular alterations with cartilage impairment that resembles joint synovitis. Thus, the toxic venom present in the caterpillar hairs interferes with the phenotype of the cells present in the joints, resulting in inflammation and promoting tissue injury. Therefore, to address the inflammatory mechanisms triggered by envenomation, we studied the effects of P. semirufa hair extract on human chondrocytes. We have selected for the investigation, cytokines, chemokines, matrix metalloproteinases (MMPs), complement components, eicosanoids, and extracellular matrix (ECM) components related to OA and RA. In addition, for measuring protein-coding mRNAs of some molecules associated with osteoarthritis (OA) and rheumatoid arthritis (RA), reverse transcription (RT) was performed followed by quantitative real-time PCR (RT-qPCR) and we performed the RNA-sequencing (RNA-seq) analysis of the chondrocytes transcriptome. In the supernatant of cell cultures treated with the extract, we observed increased IL-6, IL-8, MCP-1, prostaglandin E2, metalloproteinases (MMP-1, MMP-2, MMP-3 and MMP-13), and complement system components (C3, C4, and C5). We noticed a significant decrease in both aggrecan and type II collagen and an increase in HMGB1 protein in chondrocytes after extract treatment. RNA-seq analysis of the chondrocyte transcriptome allowed us to identify important pathways related to the inflammatory process of the disease, such as the inflammatory response, chemotaxis of immune cells and extracellular matrix (ECM) remodeling. Thus, these results suggest that components of Premolis semirufa hair have strong inflammatory potential and are able to induce cartilage degradation and ECM remodeling, promoting a disease with an osteoarthritis signature. Modulation of the signaling pathways that were identified as being involved in this pathology may be a promising approach to develop new therapeutic strategies for the control of pararamosis and other inflammatory joint diseases.